The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1108/lm-01-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Improving and extending activities of university and research libraries in Iran: the role of Iranian Research Institute for Information Science and Technology (Irandoc)

Abstract: PurposeThe purpose of this paper is to define the need to a center for improving and extending university and research libraries in Iran, and identifying capabilities and position of Iranian Research Institute for Science and Technology (Irandoc) for accepting possible roles.Design/methodology/approachThis research was documentary with scoping review in which the scope of research defined with internal and external organizational documents, related research studies in National Information System (NATIS) and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Moreover, there is no communities or Non-Governmental Organization (NGO) to step forward to engage in promote, monitor or excellence of the ARLs activities and services. Furthermore, as reported by Rajabali Beglou (2018) there is no specific departments or sections in MSRT to evaluate and monitor the activities and status of these libraries and Iranian Library & Information Science Association (ILISA) does not play important role in this regard.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there is no communities or Non-Governmental Organization (NGO) to step forward to engage in promote, monitor or excellence of the ARLs activities and services. Furthermore, as reported by Rajabali Beglou (2018) there is no specific departments or sections in MSRT to evaluate and monitor the activities and status of these libraries and Iranian Library & Information Science Association (ILISA) does not play important role in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…A look at the history of successful organizations in this area shows that in most cases the activities of an organization to improve and extend the activities of libraries are functions of an association or an NGO. Research findings of Rajabali Beglou and Akhshik (2020) also indicated that Iranian Research Institute for Information Science & Technology (Irandoc) has some activities that national and international organizations or associations usually support or perform. Furthermore, regardless of similarity of institutions, the CAUL as an association bears more similarity with in the activities performed by the Irandoc in improving and expanding these libraries.…”
Section: Introductionmentioning
confidence: 99%